Existence and multiplicity of solutions for a quasilinear double phase problem on the whole space. Issue 2 (1st February 2023) - Shen, Ji-Hong; Wang, Li-Yan; Chi, Kun; Ge, Bin
Abstract : In this paper, we consider a quasilinear double phase problem on the whole space. Some new criteria to guarantee the existence of ground states for the considered problem is established using the mountain pass theorem. Our results generalize some existing results.